In vitro investigation of antioxidant and antidiabetic properties of phenolic-rich extract from stingless bee honey (Heterotrigona itama) - Zulhilmi Cheng, Mohamad Zulhafiz Shafiq; Zawawi, Norhasnida; Ooi, Der Jiun; Chan, Kim Wei; Ismail, Norsharina; Ishak, Nur Akmal; Mohd Esa, Norhaizan (Universiti Putra Malaysia, 2023)
Introduction: The increase of Type 2 diabetes mellitus has prompted numerous research toward finding an alternative to manage the disease through the oxidant-antioxidant balance, mainly through bioactive compounds in natural products. This study explored the antioxidant and antidiabetic properties of phenolic-rich extract (PRE) from Stingless bee honey (SBH) (Heterotrigona itama) as therapeutic agent to restore the redox balance. Methods: The total phenolic content (TPC), total flavonoid content (TFC) and antioxidant assays of PRE and SBH, were determined to provide preliminary insight into the sample’s antioxidant properties, followed by high-performance liquid chromatography analysis of PRE. The antidiabetic potential of PRE and SBH were determined based on their inhibition against α-amylase and α-glucosidase enzymes. The cytotoxicity analysis of PRE was conducted on 3T3-L1 adipocytes and L6 muscle cells before the glucose uptake and cellular antioxidant analyses were performed on both cell lines, respectively. Results: PRE yielded higher TPC, TFC and antioxidant activities than SBH. The phytochemical profile of PRE comprises gallic acid, myricetin, kaempferol, epicatechin, chlorogenic acid, quercetin, syringic acid, and cinnamic acid. The results from carbohydrate enzymatic inhibitory assays collectively suggested that PRE exhibited more robust antidiabetic activities than SBH. PRE showed good glucose uptake stimulating and reactive oxygen species scavenging effects in those cell lines. Conclusion: Overall, PRE from SBH showed higher carbohydrate enzymatic inhibition, glucose uptake, and protection against intracellular oxidative stress, primarily due to its high antioxidant content and may serve as an alternative therapeutic agent for managing T2DM.